Radiochemical Purity Test of Fractionated Sestamibi Kit Labelled with Technetium-99m - Hasna Chaerunisa; N. Elly Rosilawati; Muchtaridi Muchtaridi (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Coronary Heart Disease (CHD) is a heart disorder caused by blockage of blood vessels. CHD can bedetected by Myocardial Perfusion Imaging (MPI). MPI is performed by injecting a radiopharmaceuticalinto the patient's body. 99mTc-sestamibi is a radiopharmaceutical that is commonly used in MPI.Sestamibi is available in the form of a multidose vial, but the cost of the examination will be expensiveif it is only used for one patient. Cost effectiveness can be increased by fractionating the sestamibi kitbefore labelled by 99mTc. 99mTc-sestamibi needs to be tested for quality control before it is administeredto the patients. One of the tests is the radiochemical purity test. The aim of this study was to determinethe radiochemical purity of the fractionated sestamibi kit labelled by 50 mCi 99mTc. 2 vials of sestamibikit were fractionated by adding 5 mL of 0.9% NaCl solution to each vial and divided into 10 new vials.Radiochemical purity was measured using the thin layer chromatography (TLC) method. The resultsof this study indicated that all samples had radiochemical purity of 100% up to 6 hours after labelling.